SirT3 is a nuclear NAD(+)-dependent histone deacetylase that translocates to the mitochondria upon cellular stress - Scher, Michael B. (Cold Spring Harbor Laboratory Press, 2007)
In humans, there are at least seven Sir2-like proteins (SirT1–7) with diverse functions, including the regulation of chromatin structure, and metabolism. SirT3 levels have been shown to correlate with extended life span, to localize to the mitochondria, and to be highly expressed in brown adipose tissue. In humans, SirT3 exists in two forms, a full-length protein of ∼44 kDa and a processed polypeptide lacking 142 amino acids at its N terminus. We found that SirT3 not only localizes to the mitochondria, but also to the nucleus under normal cell growth conditions. Both the full-length and processed forms of SirT3 target H4-K16 for deacetylation in vitro and can deacetylate H4-K16 in vivo when recruited to a gene. Using a highly specific antibody against the N terminus of SirT3, we found that SirT3 is transported from the nucleus to the mitochondria upon cellular stress. This includes DNA damage induced by Etoposide and UV-irradiation, as well as overexpression of SirT3 itself.